Analisis Strategi Guru Melalui Metode Mengajar di SDN 004 Samarinda Ilir (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze teacher strategies through teaching methods applied at SDN 004 Samarinda Ilir. The background of the study is based on the importance of the teacher's role in selecting and implementing appropriate teaching methods so that the learning process is more effective and in accordance with student characteristics. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation of five class teachers and the principal as supporting informants. The results of the study indicate that teachers use a combination of several methods, namely lectures, group discussions, questions and answers, and direct practice. The lecture method is more dominantly applied to conceptual subjects, while group discussions and direct practice are used in subjects that require active student participation, such as Indonesian, Mathematics, and Science. Supporting factors for this strategy include the support of the principal, the availability of simple media, and a conducive learning environment. The inhibiting factors are time constraints, variations in teacher abilities in managing the class, and low participation of some students. The discussion of the research results shows that teacher strategies at SDN 004 Samarinda Ilir have been directed towards active learning (student-centered learning), although there are still obstacles that make traditional methods more dominant. This study recommends improving teacher competency in classroom management and implementing cooperative learning models to ensure more equitable student engagement.